Examining the Compressive Behavior of SFRC and SCC Using Finite Element and Experimental Methods - Hano, Muna M.; Hano, Salwa M. A.; Al-Rawe, Hesham S. (Salehan Institute of Higher Education, 2025)
The compressive behavior of various kinds of concrete, including plain concrete, steel fiber-reinforced concrete (SFRC), and self-compacting concrete (SCC), was investigated experimentally in this paper and simulated using finite element analysis through ABAQUS software. Thirty specimens were cast and tested with two concrete compressive strengths (20 and 30 MPa). Steel fibers were added at volume fractions of (0, 0.4, and 0.75)%, while SIKA-VISCOCRETE-5930 IQ was incorporated at (0.8 and 1.8)% by weight of cement. The results showed that the compressive strength of the tested specimens increased with the increase of fibers and SIKA-VISCOCRETE-5930 IQ dosages. The FEA results exhibited a good agreement with those from the experimental work in terms of the stress-strain relationships for plain, SFRC, and SCC. A Student's t-test was performed on both experimental and FE analysis outcomes, and the difference among them was found to be statistically insignificant. The accuracy of numerical modeling in predicting concrete behavior under compression is supported by the findings of this study, and the effectiveness of steel fibers and SIKA-VISCOCRETE-5930 IQ in developing the compressive strength of concrete is also highlighted. Doi: 10.28991/CEJ-2025-011-03-017 Full Text: PDF